Peran dan Proses Berfikir Sistem dalam Konteks Pendidikan - Muhammad Chaidir; Sari Andini; Ulfa Hayana Sari Harahap; Abdul Fattah Nasution (Student Research Journal, 2024)
In the era of globalisation and rapid technological development, education systems face complex challenges that require innovative approaches. This article examines the role of systems thinking in education, which enables learners to understand the relationship between components holistically. The research method used is library research, by collecting data from various written sources to build a strong theoretical foundation. The research findings have 3 main points: 1. As a solution to complex educational problems 2 as a means of improving the quality of learning and 3 developing students’ critical thinking skills. The purpose of this research is to identify and analyse the role and process of systems thinking in education, and provide practical recommendations for educators and policy makers to improve the quality of education through the application of this approach.